TINJAUAN ASPEK PERAWATAN TERHADAP PERMASALAHAN RANTAI JANGKAR DI SPOB BUANA DYNAMIC - Aryanda Wira; Oktavera Sulistiana; Nur Indah Sari (STKIP Subang, 2026)
This study aims to analyze the implementation of the Planned Maintenance System (PMS) on the anchor chain system aboard SPOB Buana Dynamic and to identify the constraints encountered in its execution. The research method employed is a descriptive qualitative approach, with data collected through direct onboard observation, documentation, and literature review. The results indicate that the maintenance of the anchor chain system has not been carried out optimally and has not been implemented in a disciplined manner. Several maintenance procedures, such as wear inspection of components, chain stopper testing, and comprehensive inspections, are not performed routinely. This condition leads to technical problems, including corrosion and wear of the anchor chain, which may reduce the strength and reliability of the system. In addition to technical factors, managerial issues also contribute, such as inadequate planning, organization, and supervision, as well as low crew awareness regarding the importance of preventive maintenance. From a regulatory compliance perspective, the PMS implementation has not fully met the safety requirements established by international standards such as SOLAS and the ISM Code. These shortcomings impact the smooth operation of the vessel, particularly during anchoring and weighing processes. It can be concluded that the PMS implementation remains reactive and has not been optimally applied. Therefore, improvements in maintenance practices, stricter supervision, and the development of a preventive maintenance culture are necessary to enhance safety and operational reliability of the vessel).